Are Ex‐Ante Hypothetical Bias Calibration Methods Context Dependent? Evidence from Online Food Shoppers in China. Issue 2 (13th June 2018) - Lin, Wen; Ortega, David L.; Caputo, Vincenzina
Abstract : Consumers are increasingly turning to the Internet as a medium of acquiring food products. This study informs the consumer literature by assessing the effects of three ex‐ante hypothetical bias mitigation methods on Chinese consumer's stated online food shopping behavior: a cheap talk script, the solemn oath, and honesty priming. Using data from choice experiments (CEs), our analysis finds no significant differences in willingness to pay (WTP) values for select product attributes (origin, product rating, and number of reviews) between the various mitigation methods and a control group. Statistical tests and analysis provide evidence that hypothetical bias is not likely a significant concern when implementing certain studies using Internet‐based CEs to elicit marginal WTP values for online food product characteristics. We discuss how e‐commerce can better address consumer needs and explain the importance of our findings for study design and future research on consumer online food shopping behavior.